Challenges of the 21st Century in European Continent: Terrorism and Migration - Maria Bordas; Janos Tomolya (European Scientific Journal, ESJ, 2022)
At the beginning of the twenty-first century, Europe faced new challenges. These new challenges communicated in this study address two issues, terrorism, and migration. Firstly, this study seeks to answer the question, if is there a direct link between migration and terrorism using the research methodology of data collection and analysis, also, what are the secondary links between terrorism outside Europe and migration to Europe. Secondly, based upon the qualitative methodology of research, this study is analyzing European terrorism and migration to European countries with respect to how these two phenomena have affected migration policies, and governments' counter-terrorism actions. Finally, this paper tries to find an answer to the dilemma of a stricter, more restrictive migration policy versus effective fight against terrorism. This paper shows that while it is true that one root cause of migration is the threat of terror, nevertheless terror itself is not an inexplicable phenomenon or "final cause”, but a consequence of numerous roots causes.